2015
DOI: 10.4172/1948-5956.1000376
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Inhibits Cell Growth and Migration in Head and Neck Squamous Cell Carcinoma Cell Lines by Attenuating Epidermal Growth Factor Receptor Signaling

Abstract: Objective: Active components of natural foods are increasingly receiving attention for their chemopreventive and chemotherapeutic potential in a wide variety of cancers. Rosmarinic acid (RA), a phenolic compound in various herbal plants, is well-recognized for its anti-oxidant, anti-inflammatory, anti-proliferative properties in a variety of cell types. In this report, we describe a novel role for RA as an inhibitor of epidermal growth factor (EGF) stimulated signaling in HNSCC and propose a cellular reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…*P < 0.05, **P < 0.01, ***P < 0.001 determined by one-way ANOVA using Dunnet's multiple comparison test. C control, Q quercetin, RA rosmarinic acid, si siRNA cell carcinoma cell lines by inhibiting EGFR phosphorylation and MAPK signaling (Tumur et al 2015). We demonstrated in this study that RA treatment reduces Hsp27 expression and induces caspase-3-dependent apoptosis in U-87 MG cells.…”
Section: Discussionmentioning
confidence: 54%
“…*P < 0.05, **P < 0.01, ***P < 0.001 determined by one-way ANOVA using Dunnet's multiple comparison test. C control, Q quercetin, RA rosmarinic acid, si siRNA cell carcinoma cell lines by inhibiting EGFR phosphorylation and MAPK signaling (Tumur et al 2015). We demonstrated in this study that RA treatment reduces Hsp27 expression and induces caspase-3-dependent apoptosis in U-87 MG cells.…”
Section: Discussionmentioning
confidence: 54%
“…RA inhibits EGF-induced EGFR activation, leading to downregulation of PI3K/AKT and MAPK/ERK and reduction in the viability and migration of head and neck squamous cell carcinoma cell lines (Tumur et al 2015). Also, computational and theoretical data suggest RA binds directly to EGFR, acting as a pharmacological inhibitor of the receptor (Balogun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have previously demonstrated that RA can modulate HDAC expression (Ferdousi et al 2019;Jang et al 2018) and EGFR activity (Balogun et al 2021;Tumur et al 2015), which are targets for MB therapies. Although its antitumor effects against other types of central nervous system (CNS) cancer cell lines have been demonstrated (Khan et al 2019;Ramanauskiene et al 2016;Şengelen and Önay-Uçar 2018), previous studies have not examined its possible effects in MB models.…”
Section: Introductionmentioning
confidence: 99%
“…Diterpenes carnosic acid and rosmarinic acid (RA) are the main polyphenols found in rosemary extract (18) . RA have a therapeutic role, with respect to its anti-oxidant, and anti-inflammatory activities (20) . Pervious literature had described the growth inhibitory and anti-invasion properties of RA in colon, skin, breast and ovarian cancers in vitro and/or in vivo but the mechanisms underlying these effects are poorly understood (21)(22)(23)(24) .…”
Section: Introductionmentioning
confidence: 99%